Environmentally sound technologies for women in agriculture. - International Federation for Women in Agriculture; International Institute of Rural Reconstruction (New Delhi, India International Federation for Women in Agriculture, 1996)
A simple and science-based material that aims to help reduce drudgery and increase efficiency of extension workers while maintaining a clean and healthy environment. It contains topics on animal husbandry and dairying, vegetables and post harvest technologies, organic farming, and other fields of agriculture.
Jointly published with International Institute of Rural Reconstruction, Silang, Cavite.
Keywords: Agriculture -- Technology transfer; Women in agriculture -- Handbooks, manuals, etc; Agriculture -- Environmental aspects